Antispasmodics basic esters of substituted α-phenyl and α-cyclohexylpropionic or acetic acids and of substituted malonic acids - Abcede, Juanito Beltran
During this investigation a number of substituted α-phenyl- and α-cyclohexyl-β-hydroxypropionic acids, RR'C(OH)CHR''COOH, were prepared (R and R' = methyl, amyl, hexyl, tetramethylene, hexamethylene or 3-methylhexamethylene; R'' = phenyl or cyclohexyl). The substituted α-phenyl-β-hydroxypropionic acids were obtained by the interaction of the chloromagnesium salt of phenylacetic acid, C6H5CH(MgCl)COOMgCl, with the required ketone (Ivanov reaction). α-Phenyl-α-(l-hydroxycyclopentyl)-acetic acid (α-phenyl-β-β-tetrametylene-β-hydroxypropionic acid) and α-phenyl-α-(l-hydroxycycloheptyl) acetic acid were hydrogenated catalytically to the corresponding α-cyclohexyl acids.
With two exceptions, all of the β-hydroxypropionic acids were converted into crystalline β-diethylaminoethyl ester hydrochlorides by the use of the Horenstein-Pahlicke procedure; the corresponding methobromides were also prepared. Crystalline salts could not be obtained from the β-diethylaminoethyl esters of α-phenyl-β-methyl-β-n-amyl-β-hydroxypropionic and α-Phenyl-α-(l-hydroxy-4-methylcyclohexyl) acetic acids. The hydrochlorides and methobromides of the β-(l-heptamethylenimino)ethyl esters of diphenylacetic, diphenylhydroxyacetic and α-phenyl-α-(l-hydroxycycloheptyl)-acetic acids, and of the β-(l-octamethylenimino) ethyl esters of diphenylacetic and diphenylhydroxyacetic acids were synthesized.
The (β-diethylaminoethyl) esters of substituted malonic acids, RR'C(COOCH2CH2NEt2)2 (R or R' = hydrogen, n-propyl, n-hexyl, cyclopentyl, cycloheptyl or phenyl), in the form of their hydrochlorides and methobromides, were prepared. The substituted malonic acids were obtained by the malonic ester synthesis. Some difficulty was experienced in the introduction of the second substituent into the diethyl monosubstituted malonate. Since the free disubstituted malonic acids readily underwent partial decarboxylation, the diethyl disubstituted malonates were hydrolyzed to the dipotassium salts of the corresponding acids; these salts reacted with β-diethylaminoethyl chloride to form the desired esters which were then converted into their hydrochlorides and methobromides. The incidental preparation of 5-cycloheptylbarbituric acid and the unsuccessful attempts which were made to synthesize a number of compounds, or to obtain them in crystalline form, are mentioned in the appendix. The basic esters described in the dissertation are to be tested for antispasmodic activity in another laboratory.
Available to the general public.
Thesis (Doctor of Philosophy)--University of Michigan, 1955.
Keywords: Antispasmodics; Acetic acid; Malonic acid